Electrical impedance of Shiraz berries correlates with decreasing cell vitality during ripening. (5th August 2015) - Caravia, L.; Collins, C.; Tyerman, S.D.
Abstract Background and Aims Cell death in the mesocarp of Shiraz berries has been correlated with berry mass loss that occurs late in ripening and can be linked to berry composition. The current techniques to assess the level of berry cell disruption are time‐consuming and can give only relative measures. Here we test if electrical impedance of the berry, which is a function of the state of cells within, can be used to detect the loss of cell vitality. Methods and Results Shiraz berries (774 berries) from two locations (one of them over two seasons) from veraison to harvest were studied. Electrical impedance spectroscopy was performed between 100 Hz and 1 or 2 MHz of alternating current across the berry, while for each berry proportion living tissue was estimated with fluorescein diacetate. The results indicated that, from veraison to the onset of cell death, berry impedance follows the accumulation of TSS. Thereafter, impedance decreases proportionally to the extent of berry cell death. Conclusions Changes in cell vitality of the Shiraz grape berry can be objectively determined through impedance spectroscopy. The measurements also indicate that cell membranes, although becoming leaky, may still remain intact. Significance of the Study Impedance spectroscopy as applied to the grape berry has demonstrated a promising application for measuring berry composition.